Challenges of transformation of research data into open data: The perspective of social sciences and humanities. (1st September 2018) - Kelli, Aleksei; Mets, Tõnis; Vider, Kadri; Värv, Age; Jonsson, Lars; Lindén, Krister; Birštonas, Ramūnas
The authors address the transformation of research data into open data. The article draws on the experience in four countries: Sweden, Finland, Estonia and Lithuania. The transformation process presents several challenges where legal, organizational and individual aspects influence the process. Research data often contain personal data. Research data could also be covered with intellectual property (IP) rights. This means that personal data and IP regulations should be integrated into the dissemination model. While there is a potential conflict between the policies for open data that aim to make data freely available and those of an entrepreneurial university that emphasize commercialization of research results, these policies need to be made compatible. Researchers producing data are vital for reconciling the two, but they currently lack the motivation to contribute towards the implementation of the open data policy due to missing career incentives.